JURIDICAL REVIEW OF GOLD INSTALLMENT FINANCING AT INDONESIAN ISLAMIC BANKS IN THE CONTEXT OF MURABAHAH - M.Khairuzzadi; Nevi Hasnita (Prodi Hukum Ekonomi Syariah, Fakultas Syariah dan Hukum, UIN Ar-Raniry, 2025)
The development of gold installment products in sharia banking has become a popular investment alternative among the public, as it is considered safe, stable, and in accordance with sharia principles. This research aims to determine the mechanism for financing gold installments based on murabahah contracts, analyze the legal basis used, and identify the obstacles faced by both banks and customers. The research method employs an empirical juridical approach, utilizing descriptive qualitative analysis. Primary data was obtained through interviews with the bank (gold installment financing section and tellers) and eight customers, while secondary data came from literature, journals, and related regulations. The research results indicate that the gold installment financing mechanism at BSI is implemented through a murabahah contract, where the bank purchases gold from an authorized supplier and then resells it to customers, earning a profit margin agreed upon at the outset. This process is transparent and easy to understand. From a legal perspective, this financing is guided by DSN-MUI fatwa no. 21/DSN-MUI/IV/2001, OJK regulations, as well as internal bank regulations, so that they are free from elements of usury, gharar, and maisir. Obstacles that arise include delays in installments due to customers' financial conditions and a lack of understanding among some customers regarding the differences between sharia and conventional products. The bank handles this with education, reminder services, and restructuring options without fines. Thus, gold installment financing at BSI is proven to be in accordance with Sharia principles, provides a sense of security, and is beneficial for customers